Employability Skills of Information Technology University Graduates in India - Poddar, Nidhi (Digital Repository of Theses - SSBM Geneva, 2025)
This dissertation explores the employability skills of Information Technology (IT) graduates in India, focusing on the alignment between academic education and industry requirements. The study aims to ascertain the causes that lead to the inadequacy of academics in effectively bridging the gap between the skills imparted at educational institutions and those required by employers, despite awareness about the issue. The study also examines the perspectives of students, faculty and industry professionals regarding graduate readiness for the industry. Employing a mixed-method approach, the research utilizes qualitative and quantitative data collection techniques, including surveys and interviews to gather insights from various stakeholders. The findings indicate significant technical and soft skills gaps, with students expressing concerns about their lack of hands-on experience and practical application during their educational training. Faculty members reported challenges such as administrative burdens and limited industry engagement, which hinders their ability to align curricula with industry needs. Industry representatives noted that graduates often require extensive retraining, particularly in problem-solving, communication and the latest technologies. Furthermore, a noticeable discrepancy exists between students’ self-assessments of their preparedness and the employers’ assessment. This dissertation emphasises the necessity for the curriculum to be more closely aligned with industry requirements, advocates hybrid learning methods, soft skill trainings, integrating practical learning opportunities such as internships, industry collaborations and hands-on projects. It also highlights the importance of faculty development programs and sustained industry partnerships to maintain the relevance of academic training. It advocates integrating AI, digital tools and entrepreneurial training and utilising CSR funds to support the academia. This dissertation highlights the need for the government initiatives to promote shared accountability among all stakeholders, ensuring that each plays a proactive role in enhancing graduate employability. The study provides valuable recommendations for bridging the gap between academia and industry and thereby enhancing IT graduates' employability in India. Keywords: Employability, Skill Gap, Information Technology, Graduate, India